2010
DOI: 10.1007/s10649-010-9240-y
|View full text |Cite
|
Sign up to set email alerts
|

Appraising lexical bundles in mathematics classroom discourse: obligation and choice

Abstract: Working from a large corpus of transcripts from secondary mathematics classrooms, we identify patterns of speech that encode interpersonal positioning. We extend our analysis from a previous article (Herbel-Eisenmann, Wagner & Cortes, Educ Stud Math, 2010, in press), in which we introduced a concept from corpus linguistics-a "lexical bundle," which has been defined as a group of three or more words that frequently recur together, in a single group, in a particular register. In that article we noted the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 21 publications
(14 reference statements)
0
17
0
1
Order By: Relevance
“…Other work has focused on how acts of positioning enable or constrain particular student learning opportunities [31][32][33][34][35][36] (See Figure 3). For example, Wood showed that particular acts of positioning opened or closed mathematics learning opportunities [36].…”
Section: Links Between Identity and Learningmentioning
confidence: 99%
“…Other work has focused on how acts of positioning enable or constrain particular student learning opportunities [31][32][33][34][35][36] (See Figure 3). For example, Wood showed that particular acts of positioning opened or closed mathematics learning opportunities [36].…”
Section: Links Between Identity and Learningmentioning
confidence: 99%
“…In Herbel-Eisenmann and Wagner's quantitative analysis of a large corpus of mathematics classroom transcripts, two relevant authority structures were identified as pervasive [25]. They found that expressions of necessity were very prevalent in the discourse.…”
Section: Mystery In Tension With Controlmentioning
confidence: 99%
“…They did not include them in the functional analysis, however, because the contracted form makes these four-word bundles but with five word units (with the two-word contraction) developed our own categorization of the stance bundles from the SMC Corpus to identify nuances within the encoding of perspective (Herbel-Eisenmann & Wagner, 2010). Similarly, the bundles classified as encoding intention/prediction in the SMC Corpus are all personal, and over half of them do not appear in the other two corpora.…”
Section: Stance and Language Choice In Secondary Mathematics Classroomentioning
confidence: 99%
“…Second, this demonstration that the structuring of stance is central to mathematics classroom discourse makes it clear that the mathematics classroom register includes features that are not present in what many scholars see as the mathematics register-namely the pervasiveness of references to personal identity (represented by the pronoun I) and the tendency to appeal to the teacher's personal desire when requesting obligation (see Herbel-Eisenmann & Wagner, 2010, for more about this). Both of these features do not appear in school mathematics textbooks, which are part of the classroom register but may be seen as straddling the line between it and the mathematics register.…”
Section: Stance and Language Choice In Secondary Mathematics Classroomentioning
confidence: 99%